ANALISIS MODEL PENYELAMATAN PEMBIAYAAN BERKUALITAS RENDAH DAN PEMBIAYAAN BERMASALAH NASABAH TERDAMPAK COVID-19 BANK DAERAH SYARIAH - Irham Anas; Anasril Kambut (Sekolah Tinggi Ekonomi Islam (STEI) Ar-Risalah Ciamis, 2021)
Coronavirus Disease 2019 (Covid 19) has made a serious impact on the national banking industry. Financial Services Authority (OJK) has issued a relaxation policy that is expected to suppress non-performing loans/financing in national banks. This study aims to identify and assess policies, technical models and contracts from restructuring activities for customers affected by Covid 19 at Islamic Banks towards sharia principles and banking prudential principles. This Qualitative - Empirical Research concludes that the activity of restructuring activities for customers affected by Covid 19 at PT Bank Daerah Syariah is in accordance with sharia principles and banking prudential principles, a note of improvements on the side of administrative costs and the financing restructuring contract.